Swan Lake - Helprin, Mark.; Van Allsburg, Chris; Juvenile Collection (Library of Congress) (Boston : Houghton Mifflin, 1989)
A young prince and his beloved Odette struggle to protect themselves and their infant daughter from the evil Von Rothbart in this adaptation of the classic ballet.
"Ariel books."
English language and literature.
Keywords: Ballets -- Stories, plots, etc; Fantasy fiction, American; Fairy tales